Pricing Shared Appreciation Mortgages - Zhong, Yina (2006)
This paper develops a model for the valuation of shared appreciation mortgage (SAM) and examines the effect of reduction in interest rate on the mortgage duration and share of property appreciation lender charges. The recent rise in SAM availability, as a result of some secondary market financial support and prerequisite standardization, motivates a more careful consideration of the underlying SAM value. The primary difference between the SAM model and the model for general traditional mortgage is that SAM contains a call option feature. The lender's share of appreciation in SAM is essentially a call option written by the borrower to the lender, where the lender exercises the option at the time of prepayment or at the end of the mortgage.